2022
DOI: 10.1002/jsfa.11945
|View full text |Cite
|
Sign up to set email alerts
|

Peanut skin procyanidins ameliorate insulin resistance via modulation of gut microbiota and gut barrier in type 2 diabetic mice

Abstract: BACKGROUND Peanut skin procyanidins (PSP) have been shown to possess antidiabetic activities. However, the mechanism remains poorly understood due to its low bioavailability. This study aims to investigate the preventive effect of PSP on type 2 diabetes (T2D) in mice through regulating gut microbiota and gut barrier in mice with streptozotocin (STZ)‐induced T2D. During the 30 consecutive days of the study, T2D mice were administered PSP intragastrically at 75, 150 and 300 mg kg−1 body weight d−1. RESULTS PSP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Cocoa, a rich source of flavanols, improved inflammation and glucose metabolism in Zucker diabetic fatty (ZDF) rats, which was associated with increased relative abundance of Blautia , Flavobacterium , Faecalibacterium , and Oscillospira as well as decreased relative abundance of Parabacteroides and Sutterella . Analogously, recent studies discovered that peanut skin procyanidins could alleviate glycolipid metabolism in T2DM mice by altering the composition of gut microbiota …”
Section: Natural Products Targeting the Gut Microbiota In Dmmentioning
confidence: 95%
See 1 more Smart Citation
“…Cocoa, a rich source of flavanols, improved inflammation and glucose metabolism in Zucker diabetic fatty (ZDF) rats, which was associated with increased relative abundance of Blautia , Flavobacterium , Faecalibacterium , and Oscillospira as well as decreased relative abundance of Parabacteroides and Sutterella . Analogously, recent studies discovered that peanut skin procyanidins could alleviate glycolipid metabolism in T2DM mice by altering the composition of gut microbiota …”
Section: Natural Products Targeting the Gut Microbiota In Dmmentioning
confidence: 95%
“…99 Analogously, recent studies discovered that peanut skin procyanidins could alleviate glycolipid metabolism in T2DM mice by altering the composition of gut microbiota. 100 Of note, anthocyanins enhanced the hypoglycemic effect of metformin through multiple mechanisms, including remodeling of the gut microbiota, inhibition of protein tyrosine phosphatase 1B (PTP1B), and activation of the PI3K/AKT/glycogen synthase kinase 3 beta (GSK3β) signaling pathway. 101 In terms of the gut microbiota, combined treatment with anthocyanins and metformin increased the abundance of beneficial taxa such as Helicobacter, Ruminococcus, Lactobacillus, and Bifidobacterium in diabetic mice.…”
Section: Microbiota In Dmmentioning
confidence: 99%
“…These changes were reversed when HE pups were fostered by NC dams. According to published studies, a drop in Alloprevotella ( Wang J. et al, 2020 ; Wu et al, 2021 ; Zhang et al, 2021 ; Zhao et al, 2021 ; Hao et al, 2022 ; Liu et al, 2022 ) and an increase in Blautia ( Zhao et al, 2021 ; Bao et al, 2022 ) and Tyzzerella ( Li et al, 2022 ) are found in animal models of in insulin resistance or glucose intolerance. On the other hand, antidiabetic medications and bioactive compounds modulate the gut microbial community of diabetic mouse model, characterized by increased Alistipes ( Hu et al, 2019 ; Jeong et al, 2021 ; Li et al, 2021 ; Wu R. et al, 2022 ) and decreased Anaerotruncus ( Yong et al, 2022 ), Oscillibacter ( Lin et al, 2022 ; Wang et al, 2022 ), Allobaculum ( Jia et al, 2017 ; Shen et al, 2021 ; Xu et al, 2021 ; Ma et al, 2022 ), Acetatifactor ( Wu Y. et al, 2022 ) and Turicibacter ( Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their main beneficial activities lie in reducing serum glucose levels, insulin resistance and inflammation, and increasing protective glucagon-like peptide-1 (GLP-1) secretion.Liu et al ( 21) investigated how proanthocyanidins may alter intestinal flora to improve insulin resistance in gestational diabetes, which is a crucial aspect of the research of intestinal flora in diabetes. Proanthocyanidins from peanut peels can control gut flora to reduce type 2 diabetes's insulin resistance (22). Dietary changes that alter gut flora can reduce insulin resistance (23).…”
Section: Discussionmentioning
confidence: 99%